Fringing field correction of admittance model for open-ended coaxial sensor - You, Kok Yeow (2012)
This letter presents an improved method to calculate the aperture admittance for an open-ended coaxial sensor. The accuracy of the variational integral admittance equation is enhanced by adding universal lumped capacitance correction terms. The corrected capacitance is expressed as a function of aperture size, operating frequency and relative permittivity of the sample under test.